Procrastination, general self efficacy and academic achevement Among University students in Malaysia and Pakistan [electronic resource] - Muhammad Umar Khan, 1985-; Zainudin Abu Bakar, supervisor; Fakulti Pendidikan (2014)
Thesis (Sarjana Pendidikan (Psikologi Pendidikan)) - Universiti Teknologi Malaysia, 2014